Radiographic Evaluation of the Hyoid Bone Position and Pharyngeal Airway Depth in Anteroposterior Dysplasia - Chauhan, Rajat (Int J Clin Pediatr Dent, 2019)
INTRODUCTION: The pharyngeal airway, tongue, and hyoid bone are correlated. The hyoid bone is connected to the pharynx, mandible, and cranium through muscles and ligaments and its position with respect to them determines the tongue posture and function. It also plays an important role in maintaining the airway and upright natural head position. Different skeletal patterns have different morphologies and shapes of the mandible, which might be affected by the position of the hyoid bone and the pharyngeal airway depth. This cephalometric study was conducted to relate the pharyngeal airway depth and the hyoid bone position of different skeletal patterns in sagittal dimension, and it determines and compares the linear parameters of the pharyngeal airway depth in Class I, II, and III malocclusion groups and anteroposterior, vertical, and angular positions of the hyoid bone positions in Class I, II, and III malocclusion groups. MATERIALS AND METHODS: Lateral cephalometric radiographs selected for study were divided into three groups of 30 samples each based on ANB angle and β angle into skeletal Class I, Class II, and Class III, respectively. Five linear measurements for the pharyngeal airway depth, four linear measurements for anteroposterior position, two linear measurements for vertical position, and one angular measurement for angular hyoid bone position were made. RESULTS: The pharyngeal airway depth was found to show no statistically significant difference between Class I and Class III malocclusions. The pharyngeal airway depth in Class II malocclusion was found to be statistically smaller at D1 as compared to that in Class I and Class III malocclusions, whereas it remained the same at the rest of the locations measured, i.e., D2, D3, D4, and D5. The Class III malocclusion group showed a significant statistical difference in the anteroposterior hyoid bone position at all levels (i.e., H1, H2, H3, and H4) as compared to the Class II malocclusion group, whereas it showed a statistically significant difference as compared to the Class I malocclusion group at H1 and H3. The angular inclination of the hyoid bone in the Class II malocclusion group showed a statistically significant difference with the Class I and Class III malocclusion group but the Class III malocclusion group showed no significant difference statistically when compared to the Class I malocclusion group. CONCLUSION: The pharyngeal airway depth in the Class II malocclusion group was also found to be narrower at the superiormost level measured at the posterior nasal spine from the posterior pharyngeal wall. The hyoid bone position was variable in angular and anteroposterior dimensions among different malocclusion groups. HOW TO CITE THIS ARTICLE: Chauhan R, Bagga DK, et al. Radiographic Evaluation of the Hyoid Bone Position and Pharyngeal Airway Depth in Anteroposterior Dysplasia. Int J Clin Pediatr Dent 2019;12(2):101–106.